Fat tissue engineering : development of hybrid fat grafts - Ting, Hui Lin (2015)
Adipose tissue engineering requires the use of adipocytes of recently the more common adipose-derived stem cells (ASCs). In an attempt to mimic the native adipose tissue microenvironment, Alg-gel scaffolds were optimized and fabricated with stiffness close to that of in vivo adipose tissues. Both Alg and Gel are natural biomaterials which are non-toxic and can be crosslinked to produce a hybrid scaffold. The eventual aim was for the encapsulation of ASCs in 3D Alg-gel scaffolds with practical applications such as hybrid fat grafts for tissue engineering. A comparative cell study was conducted using HEK293FT and a control system using 2D cell cultures. The chemical, mechanical and structural properties of the hybrid scaffolds were studied using the FTIR and the Rheological testing methods. Subsequently, cellular studies such as proliferation and viability assays were carried out. The study suggested that higher gelatin concentration in the scaffolds could provide a better chance of cell attachment for proliferation and hence promote survival in a 3D environment. Whereas, in the case of 2D Alg-gel scaffolds, the gelatin is not presented on the surface and hence subsequent cell attachment and proliferation is affected.